2013
DOI: 10.1590/s1516-14392013005000070
|View full text |Cite
|
Sign up to set email alerts
|

The improved arrhenius model with variable parameters of flow behavior characterizing for the as-cast AZ80 magnesium alloy

Abstract: In order to study the hot working behaviour of as-cast AZ80 magnesium alloy, a series of isothermal upsetting tests with height reduction of 60% were performed at the temperature range of 523-673 K and the strain rate range of 0.01-10 s -1 on a servo-hydraulic Gleeble-1500 machine simulator. Based on the regression analysis for Arrhenius type equation of flow stress, the activation energy of deformation was determined to be Q = 168.6606 KJ·mol -1 , and material constants A, n and α in the equation also were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Also, some similar http://dx.doi.org/10.1016/j.matdes.2014.02.052 0261-3069/Ó 2014 Elsevier Ltd. All rights reserved. constitutive equations were established for the novel bimetal consisting of pearlitic steel and low carbon steel [35], AISI 420 stainless steel [36], GCr15 steel [37], Sanicro-28 super-austenitic stainless steel [38], Ni-42.5Ti-3Cu alloy [39], as-cast Ti-43Al-4Nb-1.4W-0.6B alloy [40], Al-3Cu-0.5Sc alloy [41], spray-deposited Al-Zn-Mg-Cu alloy [42], as-cast AZ80 magnesium alloy [43], cast A356 aluminum alloy [44], 42CrMo steel [45], near-a titanium alloy IMI834 [46], and pure titanium [47]. Additionally, based on the combination of the Arrhenius-type model and Hensel-Spittel Hensel-Spittel equation, Spigarelli and El Mehtedi [48] developed a new constitutive model to describe the plastic flow behavior of AA6005 aluminum alloy tested in torsion.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some similar http://dx.doi.org/10.1016/j.matdes.2014.02.052 0261-3069/Ó 2014 Elsevier Ltd. All rights reserved. constitutive equations were established for the novel bimetal consisting of pearlitic steel and low carbon steel [35], AISI 420 stainless steel [36], GCr15 steel [37], Sanicro-28 super-austenitic stainless steel [38], Ni-42.5Ti-3Cu alloy [39], as-cast Ti-43Al-4Nb-1.4W-0.6B alloy [40], Al-3Cu-0.5Sc alloy [41], spray-deposited Al-Zn-Mg-Cu alloy [42], as-cast AZ80 magnesium alloy [43], cast A356 aluminum alloy [44], 42CrMo steel [45], near-a titanium alloy IMI834 [46], and pure titanium [47]. Additionally, based on the combination of the Arrhenius-type model and Hensel-Spittel Hensel-Spittel equation, Spigarelli and El Mehtedi [48] developed a new constitutive model to describe the plastic flow behavior of AA6005 aluminum alloy tested in torsion.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al 21 and Quan et al 22 revised the strain-dependent hyperbolic sine constitutive models by incorporating the hot forming parameters (such as material constants n and a, and structure factor A, activation energy of deformation Q). Other kinds of phenomenological constitutive models include Khan-Huang-Liang (KHL), and Johnson-Cook (JC) etc., showing large differences of accuracy in different range of temperatures and strain rates 16,23,24 .…”
Section: Modelling the Hot Flow Behaviors Of Az80 Alloy By Bp-ann Andmentioning
confidence: 99%
“…Lin et al 45,46 presented a modified hyperbolic sine constitutive equation, in which the hot forming parameters (such as Q, n, a, and A) as functions of strain were incorporated in the improved the Arrhenius-type constitutive equation. Quan et al 22 calculated a series of coefficients (Q, n, A, and a) shown in Table 2 …”
Section: Existing Improved Arrhenius-type Constitutive Model For Az80mentioning
confidence: 99%
“…Recently, the Arrhenius-type equation and their revised forms of phenomenological models were utilized to model the hot flow behaviors of many materials, such as Ti-6Al-4V 15 ,Ti60 16 , and pure titanium 17 , etc. Lin et al 18,19 and Quan et al 20 improved the initial Arrhenius-type equations by incorporating strain and some material parameters (such as structure factor A and activation energy of deformation Q) to obtain more accurate Arrhenius-type equation. Other phenomenological constitutive models involve the typical Johnson-Cook (JC) model and Khan-Huang-Liang (KHL) model etc., however, they exhibit large accuracy deviations at different strain rates and temperatures [21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%